The Role of Madrasah Principal's Managerial Competency and Professional Teacher Competency in Improving Students' Academic Achievement: A Literature Review - Putri, Indah Renjani; Muhammad, Muhammad; Agus, Agus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
. Improvements in the quality of education in madrasahs are greatly influenced by the quality of teacher leadership and teacher professionalism, especially in relation to student academic achievement. The reality before us shows that madrasahs face various challenges, such as limited resources, a lack of innovative learning strategies, and differences in quality between facilities. Therefore, this study aims to examine the influence of principal management competence on student academic achievement, describe the role of professional teachers in improving academic achievement, and explore the relationship between these two factors. This study also aims to examine the quality of education in madrasahs. This study applies a literature research method with a content analysis approach to relevant books, articles, and scientific journals. The findings show that principals with good management skills are able to create a conducive learning environment, while professional teachers are a key factor in delivering effective and meaningful teaching. The synergy between the two creates a positive and sustainable academic culture that ultimately leads to improved student achievement. It is hoped that these findings will contribute to the literature on educational management and provide practical contributions to educators, teachers, and policy makers in developing strategies to improve the quality of madrasahs in a global context.